Co-governance, Transregional Maritime Conventions, and Indigenous Customary Practices Among Subsistence Fishermen in Ende, Indonesia - Ramenzoni, Victoria C. (Frontiers in Marine Science, 2021)
This article presents a case study of a fishery in the port-town community of Ende, Flores, a former littoral hub located at the periphery of major commercial systems in the Indo-Pacific region. The article argues that more attention be paid to the role of transregional maritime networks, nautical conventions, and navigational practices embedded within local tenure systems to understand the apparent absence of formal control of marine and coastal resources. Through ethnographic and archival research, this study identifies the presence of indigenous institutions for fishing grounds regulation and documents the existence of broader transregional norms dictating proper fishing and navigation. Exploring the interactions between more pluralistic customary systems that exist in port-towns such as Ende and recent fishery development policies, the article discusses some of the obstacles to implementing sustainable co-management strategies. While the Indonesian central government is strongly promoting co-governance approaches for resource management, these institutional models are based on geographically narrow definitions of tradition and customary law which can lead to management failures, such as elite capture and local fishers’ disenfranchisement. In this case, policies emphasize the formation of cooperative groups without considering transregional beliefs about independence and pre-established systems of obligations. As a result, disputes among the fishermen, conflicts with local fishery officers, and the use of non-sustainable practices continue. For example, embodying predominant Southeast Asian beliefs, Endenese are known for their entrepreneurial nature and strong self-sufficiency ethos. Yet, these notions are ignored by local government agencies that view the fishermen as selfish and disorganized. In order to formulate true participatory solutions, a careful assessment of the role played by transregional perspectives that go beyond geographically localized understandings of customary practices is needed. The article concludes with a consideration of the role played by decentralization processes, subsidies, and aid programs in entrenching poverty and inequality among local communities.